Peaceful Mutual Harmonious Practical Accommodation of the Claims of the other in Israel/Palestine (London Journal of Research In Humanities and Social Sciences, 2023)
What is good for my Family' ( KIN Altruism)and 'What is good for my Business' (Reciprocal Altruism) are the primary motivators of 'human Organic Natural Intelligence' (ONI) in social behavior. Concern forunrelated Others designated 'Empathetic Altruism' was pursued in civilization by spiritual leaders. Each had some followers, but ONI was not able to accept different practices without conflict. In Nature Strong Artificial Intelligence (SAI) has emerged in inorganic Silicon, probably to overcome the structural deficiencies of ONI. Nature Is the final arbiter in evolutionary change. However Global Decision Making (GDM) by ONI continues, resulting in much human suffering everywhere. If an accommodation in the contest between ONI and SAI can be arrived at, then people can live in peace in a constructive manner. Toward this end, the current article explores how the peaceful coexistence between ONI and SAI can be achieved.